ЦИКЛЫ В ГЕОЛОГИИ - Вылцан И.А.; Устинова В.Н. (My University, 2004)
Geological cycles may be considered as reflection of continuous-discontinued process of lithosphere evolution. Its structure and composition are characterized by hierarchically related geological bodies, which makes it possible not only to reveal subordination between small and large sub-divisions, but also to carry out their natural ranking and correlation.
Keywords: 551.3:550.834